Mutations in Homocysteine Metabolism Genes Increase Keratin N-Homocysteinylation and Damage in Mice - Kamila Borowczyk; Jacek Wróblewski; Joanna Suliburska; Noriyuki Akahoshi; Isao Ishii; Hieronim Jakubowski (International Journal of Genomics)
Genetic or nutritional deficiencies in homocysteine (Hcy) metabolism increase Hcy-thiolactone, which causes protein damage by forming isopetide bonds with lysine residues, generating N-Hcy-protein. In the present work, we studied the prevalence and genetic determinants of keratin damage caused by homocysteinylation. We found that in mammals and birds, 35 to 98% of Hcy was bound to hair keratin via amide or isopeptide bond (Hcy-keratin), while 2 to 65% was S-Hcy-keratin. A major fraction of hair Hcy-keratin (56% to 93%), significantly higher in birds than in mammals, was sodium dodecyl sulfate-insoluble. Genetic hyperhomocysteinemia significantly increased N-Hcy-keratin levels in the mouse pelage. N-Hcy-keratin was elevated 3.5-, 6.3-, and 11.7-fold in hair from Mthfr−/−, Cse−/−, or Cbs−/− mice, respectively. The accumulation of N-Hcy in hair keratin led to a progressive reduction of N-Hcy-keratin solubility in sodium dodecyl sulfate, from 0.39 ± 0.04 in wild-type mice to 0.19 ± 0.03, 0.14 ± 0.01, and 0.07 ± 0.03 in Mthfr−/−, Cse−/−, or Cbs−/−animals, respectively. N-Hcy-keratin accelerated aggregation of unmodified keratin in Cbs−/− mouse hair. Keratin methionine, copper, and iron levels in mouse hair were not affected by hyperhomocysteinemia. These findings provide evidence that pelage keratin is N-homocysteinylated in vivo in mammals and birds, and that this process causes keratin damage, manifested by a reduced solubility.